The Level of Aggressiveness During Karate Practice of Inmates in Correctional Settings - Frigout, Jérôme; Degrenne, Olivier; Delafontaine, Arnaud (Frontiers in Psychology, 2020)
Karate is known to enhance cognitive functioning, emotional well-being and self-regulation, and to contribute to an overall behaviour rehabilitation process. However, little data is available on the impact of practicing karate in adult prison inmates. The main objective of this research was to evaluate aggressive behaviour, comparing prison inmates and club practitioners during karate practice. The level of aggressiveness was rated by observers during defined elements and training situations in karate classes held in France. Data were collected during 77 observations of 75 prison inmates (55 male and 20 female) in a prison setting, and 188 observations of 117 club practitioners (80 male and 37 female) in a club setting over a period of 26 months. Licit aggressiveness was graded by observers during launched actions, kiais and bows, and the practice level (belts) was also considered. Interrater reliability of the observational measure was highly acceptable (Cohens' kappa =1). Comparisons between female and male prison inmates and club practitioners were made using the non-parametric Mann-Whitney U test for independent samples. The results revealed that a higher level of aggressiveness was observed in both male and female club practitioners during launched actions and kiais than in prison inmate practitioners (p<.001, small effect size). However, prison inmates (of both genders) showed a higher level of aggressiveness during bows (p<.001, medium effect size). While the analyses showed no significant differences between genders, the level of karate practice was associated with distinct changes. Significant differences in observed aggressiveness were present only in beginners and in those with a low level of karate practice, while no differences in aggressiveness between prison or club practitioners were observed during karate practice in those with a high level of karate practice (black belt). However, these results must be interpreted with caution as there was no way to control the multiple factors that might also affect inmate behaviours in a correctional setting. We suggest that karate practice in prison may positively contribute to interactional behaviours.